Filipino textiles conservation and preservation. - Elvena, Evelyn (SPAFA Journal : a publication of the SEAMEO Regional Centre for Archaelogy and Fine Arts)
Evelyn Elvena, textile conservator of the National Museum of the Philippines, reports on the characteristics of Filipino textiles, weaving patterns, conservation and preservation techniques, status of ethno-archaeology and future plans of the museum for collections...